Earnings inequality in Germany: A decomposition-analysis - Ulrike Stein (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Several studies have shown that income inequality has risen in Germany until 2005. Less focus was put on the rise of earnings inequality which continued to rise until 2010. We distinguish different groups in the labour market with respect to working-time, gender and region by exploiting data from the German Socio-Economic panel (SOEP) for the years 1995 till 2014. Using the decomposition of the Theil1-index we demonstrate that the increase in earnings inequality is primarily the result of diverging average earnings of the various groups in the labour market (between-group inequality) and to some extent due to increasing earnings heterogeneity within groups (within-group inequality). The former effect is larger than the latter. Without the inequality reducing effect on earnings inequality due to the continuous decrease in the share of full-time working employees and the increase in the female labour participation rate (compositional effect) earnings inequality would have actually further increased after 2010. Independent of the policy target, policy measures to reduce inequality need always to be designed in such a way that they take the whole work force into account in order to achieve measurable effects.
Keywords: D31; J21; J39; 330; earnings inequality; Theil decomposition; part-time employment; female participation rate; German Socio-Economic Panel (SOEP)